Promoting Officer Integrity Through Early Engagements and Procedural Justice in Seattle, Washington, 2013 - Owens, Emily ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. For this study, researchers conducted an experimental evaluation of a training program aimed at promoting the use of procedural justice by officers in the Seattle Police Department (SPD). After identifying eligible officers using a specially designed High Risk Circumstance (HRC) model, researchers arranged non-disciplinary supervisory meetings for participants in which procedural justice behaviors were modeled. Participating officers were then asked to fill out comment cards about the experience. Using the control and engagement groups, researchers evaluated the impact that procedural justice training had on a number of outcomes including arrests, warnings and citations, use of force, and citizen complaints. In addition to participant comment cards, researchers assessed outcomes by analyzing the administrative data collected by the Seattle Police Department.